Customization of manual wheelchair components: a state-of-the-art review - Sameer More; Michelle Dunn; Shannon A. Rios; Rachael McDonald (Journal of NeuroEngineering and Rehabilitation)
Abstract Custom wheelchairs, tailored to users’ unique needs, have gained increasing attention because of their potential to increase mobility, comfort, and overall quality of life for the people using them. Employing a state-of-the-art review methodology, this literature review systematically categorizes the existing body of research on the design and manufacture of customizable manual wheelchair components, identifies current practices, and suggests areas for further research. We found that the literature to date has focused on the design and manufacture of custom-contoured cushions, and few studies have focused on other components or wheelchair customization as a whole. Technological advances in the past decade have seen the move from manual, time-consuming customization processes to digital workflows with the support of design tools. Advanced technologies such as 3D scanning, parametric modeling, product configuration systems, and finite element analysis have emerged as tools for enhancing the performance and aesthetics of wheelchair components. While the published literature provides a valuable foundation, the field of wheelchair customization is rapidly evolving, driven by ongoing innovations from manufacturers. This review highlights the need for further research to bridge the gap between academic knowledge and real-world progress in the design and manufacturing of custom manual wheelchairs.